Hemodynamic monitoring using echocardiography in the critically ill - Backer, Daniel de.; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
The hemodynamic evaluation of patients with acute circulatory failure and respiratory failure has in the past usually been performed using invasive procedures but in recent years less invasive monitoring devices have been introduced. Hemodynamic evaluation by echocardiography is based on the integration of simple indices that can be easily acquired within a few minutes at the bedside. Echocardiography can be used for both the diagnosis and the management of circulatory and respiratory failure. This book provides all the essential information required by readers in order to perform optimal hemodynamic management of the critically ill based on echocardiographic guidance. After an introductory section on basic principles, hemodynamic assessment using echocardiography is discussed in detail. The diagnosis and management of all types of circulatory and acute respiratory failure by means of echocardiography are then rigorously considered, and specific situations such as thoracic trauma and acute aortic syndrome are examined. The final section is devoted to future issues and applications.
Principles of Ultrasounds and Principal Views -- Transthoracic Echocardiography: Normal Two-Dimensional and Doppler Imaging -- Transesophageal Echocardiography: Principal Views -- Echocardiography in the Critically Ill: An Overview -- Echocardiography in the Critically Ill: An Overview -- Heart-Lung Interactions in Mechanical Ventilation -- Measurement of Stroke Volume and Cardiac Output Using Echocardiography and Doppler -- Assessment of Fluid Requirements: Fluid Responsiveness -- Assessment of Fluid Requirements: Fluid Responsiveness -- Evaluation of Left Ventricular Systolic Function -- Evaluation of Left Ventricular Systolic Function -- Hemodynamic Evaluation in the Patient with Arrhythmias -- Diagnosis and Management of Circulatory Failure -- Diagnosing the Mechanisms of Circulatory Failure -- Septic Shock -- Cardiogenic Shock Associated with Acute Left-Heart Failure -- Echocardiographic Evaluation and Monitoring of Right Ventricular Function and Pulmonary Artery Pressures -- Pericardial Effusion and Cardiac Tamponade -- Echocardiography and Extracorporeal Life Support in Intensive Care Unit -- Diagnosis and Management of Acute Respiratory Failure -- Pulmonary Edema: Which Role for Echocardiography in the Diagnostic Workup? -- Why and How to Use Echocardiography in Acute Respiratory Distress Syndrome -- Specific Situations -- Thoracic Trauma -- Hemodynamic Instability in Cardiac Surgical Patients -- Acute Aortic Syndrome: Acute Aortic Diseases in Hemodynamically Unstable Patients -- Outlook -- Learning and Competence in Critical Care Echocardiography -- Ehocardiography Alone or Coupled with Other Hemodynamic Devices? -- Future Applications.
Electronic reproduction.
Keywords: Hemodynamic monitoring; Echocardiography; Electronic books